A Critical review of “Talamzae Ghalib” by Malik Raam - Zaib-un-Nisa; Dr.Zafar Hussain Haral (Zaban-o-Adab, 2021)
Mirza Asadullah Khan Ghalib is not unknown in the history of Urdu literature. He is the Poet.The teacher of poets and father of Urdu poetry. Malik Raam is a researcher, critic, essay writer and sketch writer. His compilation of the book”Talmzae Ghalib”contains thelist & short biography of Ghalib’s pupils. It was the time when Mughal Empire was falling and British took over the charge of government by hook or crook. The literature especially the poetry portrays that time in symbolic way. Malik Ram tried his best to collect the correct data.